Trade liberalization, market reforms and competitiveness of Indian dairy sector - Sharma, Vijay Paul; Gulati, Ashok (International Food Policy Research Institute, 2003)
From chronic shortages of milk, India has emerged today as the largest producer of milk in the world crossing 80 million tonnes (GOI, 2002). This success story of Indian milk production has been written primarily by millions of smallholder producers, who dot the landscape of milk production in the country. Although the yields have remained quite low compared to the world standards yet it has not only survived but also flourished. Several factors appear to have helped it flourish. The Operation Flood one of the world s largest dairy development programs, which helped to create strong network and linkages among millions of smallholder producers, processors and urban consumers, was an important instrument in achieving this success. It is well known that all this happened under autarky and highly regulated domestic markets. The commercial imports and exports of almost all dairy products had been banned for most of the time and processing activity had been controlled through licensing which favored cooperatives over private entrepreneurs.